Retrieval cues and release from proactive inhibition - Gardiner, John M.; Craik, Fergus I.M.; Birtwistle, John (Journal of Verbal Learning and Verbal Behavior, 1972)
The present experiment attempted to specify the locus and nature of the “release from PI” phenomenon. On the critical trial, the material to be remembered (word triads) shifted from one subset of a larger category to another subset. No release was found when subjects were provided with the general category name as a retrieval cue, but release was obtained when the appropriate subset name was given as a cue at presentation. A similar release effect was obtained when the subset cue was presented at retrieval. The results favor a retrieval explanation of the release phenomenon although it is unclear whether cues increase accessibility to the TBR material or, rather, help to discriminate current from previous items.